Context and Implications Document for: Diversity and complexity: Becoming a teacher in England in 2015–2016. Issue 1 (15th February 2018) - Whiting, Caroline; Whitty, Geoff; Menter, Ian; Black, Pat; Hordern, Jim; Parfitt, Anne; Reynolds, Kate; Sorensen, Nick
Abstract : This guide accompanies the following article: Whiting, C., Whitty, G., Menter, I., Black, P., Hordern, J., Parfitt, A., Reynolds, K. & Sorensen, N. Diversity and complexity: Becoming a teacher in England in 2015–2016. Review of Education, https://doi.org/10.1002/rev3.3108